Strategies to promote science communication: organisation and evaluation of a workshop to improve the communication between Portuguese researchers, the media and the public - Bettencourt-Dias, Mónica (2004)
As western societies become increasingly dependent on scientific and technological developments, the full exercise of citizenship requires the ability to understand those developments. Scientists should be able to make this progress meaningful to different communities and to discuss its implications. However, science communication is still not part of the formal education of researchers. We organized a pioneering workshop in Portugal, Comunicar Ciência (‘Comunicating Science’), at the Gulbenkian Institute of Science (10-12 September 2003). In this workshop, 17 Portuguese scientists, from PhD students to heads of research institutes, experienced a plethora of practical exercises organised by journalists and science communication experts from Portugal and the UK. Summary and follow-up evaluations show that scientists feel more confident in their communication skills and ability to participate in activities after the workshop. This work suggests that when targeting the right people, a small, low budget activity, such as this science communication workshop, can improve the participation of scientists in science communication activities.